Genesis of the Cultural Landscape of Urals and Siberia. Issue 2 (July 2013) - Fedorov, Roman
This article presents the author's approach to the study of cultural landscape genesis. Historical and geographical reconstruction of Urals and Siberia served as the empirical basis of the study. A hypothesis that highlights some of the basic morphological components of the cultural landscape on the scale of a given region is set forth based on that reconstruction. Communications and cultural values have been classified as the primary morphological components. The article compares the cultural landscape's communicative structure and two main forms of communication. The first form includes land communication routes and regional settlement patterns, which establish a kind of communicative framework for the cultural landscape of the region. The second form is the circle of social and cultural interactions that directly or indirectly affect the economic development and life activities of regional communities. Each of these forms of communication reflects a certain pattern of cultural values that is specific to a given form of economic development in a geographical region or to a particular historical era. Using this approach, the article studies the spatial organization of the cultural landscape of the Urals and Siberia in an attempt to explain the cultural diversity of various parts of present-day Russia.